2015
DOI: 10.1056/nejmoa1500704
|View full text |Cite
|
Sign up to set email alerts
|

Age of Transfused Blood in Critically Ill Adults

Abstract: Transfusion of fresh red cells, as compared with standard-issue red cells, did not decrease the 90-day mortality among critically ill adults. (Funded by the Canadian Institutes of Health Research and others; Current Controlled Trials number, ISRCTN44878718.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
414
1
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 498 publications
(457 citation statements)
references
References 35 publications
22
414
1
13
Order By: Relevance
“…This cohort was analysed, and the trial was published based on follow-up data for up to 90 days (the primary end point). 31 During recruitment, it was clear that the UK target sample of 500 patients would not be achieved by the time that the international trial completed recruitment. In order to acquire sufficient data to maximise the value of the economic evaluation, we sought agreement from the international ABLE TSC, the funder (the NIHR HTA programme) and ethics committees to continue recruitment in UK centres until the main database was locked for analysis.…”
Section: Uk Analysis In the Context Of The International Age Of Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…This cohort was analysed, and the trial was published based on follow-up data for up to 90 days (the primary end point). 31 During recruitment, it was clear that the UK target sample of 500 patients would not be achieved by the time that the international trial completed recruitment. In order to acquire sufficient data to maximise the value of the economic evaluation, we sought agreement from the international ABLE TSC, the funder (the NIHR HTA programme) and ethics committees to continue recruitment in UK centres until the main database was locked for analysis.…”
Section: Uk Analysis In the Context Of The International Age Of Bloodmentioning
confidence: 99%
“…he results of the international ABLE trial, which included the majority of the UK cohort of patients, have been published previously. 31 We present here a summary of the UK cohort, with comparison with effects observed in the main trial cohort. The UK cohort was underpowered for the primary and secondary trial outcomes, as expected from the outset of the project, but comparison with the main trial is useful to understand any possible differences between the UK cohort and the international trial population.…”
Section: Follow-upmentioning
confidence: 99%
“…10 Recently, several randomized controlled trials, in particular in clinical settings, have been completed, and no difference was observed between groups. [11][12][13] There remains considerable debate surrounding this issue; 14 however, this is unrelated to the goal of providing the best RBC units available, and to storing RBCs so as to generate the most efficacious product. The goal of the current study is to elucidate donor biology that affects RBC storage, and the ability of the RBC to circulate post transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic blood transfusions carry inherent risk [5], and studies have increasingly linked transfusions with adverse clinical patient outcomes, including health care-associated infection [6], morbidity, and mortality [7][8][9], possibly related to storage lesions due to impairment of red blood cell (RBC) in the O 2 -dependent regulation of blood flow (hypoxic vasodilatation) [10]. Results of two recently published trials [11,12] found no differences in clinical patient outcomes for patients who received fresher (7-10 days) vs. older (more than 21 days) RBC; however, two additional trials are pending or in progress [13,14]. To curtail inappropriate and potentially injurious transfusions, accreditation agencies including AABB and The Joint Commission (TJC) have initiated in Patient Blood Management (PBM), programs to promote restrictive transfusion practices [15,16].…”
Section: Introductionmentioning
confidence: 99%